PERAN KELOMPOK TANI DALAM PENINGKATAN STATUS SOSIAL EKONOMI PETANI PADI SAWAH (Studi Kasus di Desa Sari Nadi, Kecamatan Kota Bangun, Kabupaten Kutai Kartanegara) (The Role of Farmers Group in Improving the Social-economic Status of Lowland Paddy Farmer (Case Study in Sari Nadi Village, Kota Bangun Subregency, Kutai Kartanegara Regency)) - RIFKI ARBIAN HIDAYAT; SYARIFAH MARYAM; SYARIFAH AIDA (JURNAL AGRIBISNIS DAN KOMUNIKASI PERTANIAN (Journal of Agribusiness and Agricultural Communication), 2022)
Paddy is a food crop that is widely cultivated by farmers as farmers group members in Sari Nadi Village. This study aimed to determine the role of farmer group in improving the socio-economic status of lowland rice farmer before and after becoming member of farmers group. This research was conducted from March to August 2020 in Sari Nadi Village, Kota Bangun Regency, Kutai Kartanegara Regency. Determination of the sample number used the proportional sampling method. The data were analyzed by using descriptive method. Farmers group plays a role in improving the socio-economic status of lowland rice farmer with a total score of 1,283 and an average of 33.76. The socio-economic status of farmer before becoming member of a farmers group was low and increase become high after becoming a member of a farmers group.